OCHRONA INTERESU POKRZYWDZONEGO W POLSKIM PRAWIE KARNYM - Borowicka, Monika (Zeszyty Prawnicze, 2017)
PROTECTION OF VICTIM’S RIGHTS IN THE POLISH PENAL LAW Summary The World Victimology Society was formed in 1979. That event greatly influenced the development of a study o f a victim and also initiated the movement for the wronged. Victim surveys conducted on the basis of self reporting enabled to define the concepts o f primary and secondary victimization. The surveys confirmed the fact that the implementation of an injured party protection is still inadequate. That subject matter was taken up by the VI Congress of the United Nations in 1985. The U N proclaimed the Declaration of Basic Laws for Victims of Crime and Abuse o f Authorities. In the part devoted to victims of crimes it lists four fundamental rights: a) a right of access to an administration of justice; b) a right to restoration; c) a right to compensation; d) a right to aid. The document also indicates the possibility to use mediation, arbitration, or conciliation and also the Polish legislator perceives the new trends o f punishment policy expressed in progressive regulations. As distinct from the hitherto role o f an injured party as a witness in his own case these regulations aim at securing an effective influence of an injured party on the course o f proceedings and a possibility to satisfy his claim. Currently, one o f the aims o f the Penal Code is an obligation to compensate for damages and to redress an injury sustained by an injured party. It is on the list of means of punishment together with a sanction imposing a payment to an injured or to the public purse and a pecuniary performance (article 39, point 5 of the Penal Code). It may not only complement a punishment, but also be its alternative. An obligation o f a perpetrator of an offence to redress an inflicted damage should also serve the appeasement of conflicts resulting from an unlawful conduct. It also allows a release on probation and an extraordinary mitigation of penalty. Therefore it serves a number of penal functions: o f compensation, resocialization, and education.